2012
DOI: 10.1177/0956797612439069
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Versus Metabolic Effects of Carbohydrates on Self-Control

Abstract: Self-control is critical for achievement and well-being. However, people's capacity for selfcontrol is limited and becomes depleted through use. One prominent explanation for this depletion is that self-control consumes energy in the form of carbohydrate metabolization and further suggests that ingesting carbohydrates improves self-control. Some evidence has supported this energy model, but given the broad implications of the model for efforts to improve self-control, the present research reevaluated the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(219 citation statements)
references
References 38 publications
9
210
0
Order By: Relevance
“…Moreover, human research has reported task general effects (Molden et al, 2012, Sanders et al, 2012Hagger and Chatzisarantis, 2013). An initial act of self-control by humans affects persistence, as it does performance of the Stroop task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, human research has reported task general effects (Molden et al, 2012, Sanders et al, 2012Hagger and Chatzisarantis, 2013). An initial act of self-control by humans affects persistence, as it does performance of the Stroop task.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a recent series of experiments by Molden et al (2012) have challenged this metabolic hypothesis by investigating whether self-control exertion by humans reliably depletes systemic glucose levels and whether increases in blood glucose levels are necessary to observe the replenishment of persistence. Their results suggest that there are no self-regulatory induced decreases in blood glucose levels for participants who are food restricted for 4 hrs and tested in the evening with a perceptual vigilance task.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, emerging findings showed that self-control is not energetically dependent as initially proposed (Dang 2016b;Kurzban 2010;Molden et al 2012). For example, recent meta-analytic evidence (Carter and McCullough 2014;Carter et al 2015;Hagger and Chatzisarantis 2016) does not support the proposition that self-control relies on a limited resource, when tested in laboratory settings.…”
Section: Self-control and Ego Depletionmentioning
confidence: 98%